Significance of DMBT1 in Papillary Thyroid Carcinoma Concurrent With Hashimoto’s Thyroiditis - Gan, Xiao-xiong; Li, Ya-yi; Li, Si-jin; Mo, Shi-sen; Feng, Jian-hua; Shen, Fei; Cai, Wen-song; Lai, Ye-qian; Xu, Bo (Frontiers in Oncology, 2021)
Background: Papillary thyroid carcinoma (PTC) concurrent with Hashimoto's thyroiditis (HT) was associated with better clinical prognosis. The purpose of this study was to investigate whether the differential gene expression between PTC concurrent with HT and simple PTC, and the existence of a protective gene. Material/Methods: The data of PTC were obtained from The Cancer Genome Atlas (TCGA) database. And the validation data of tissue specimens were collected from Guangzhou First People's Hospital. The thyroid tissue sections were hybridized with deleted in malignant brain tumors 1(DMBT1) probes by situ hybridization. Survival rates were analyzed by using Kaplan-Meier curves and the log-rank test was used to compare group survival rates. Prognosis clinicopathological factors were analyzed by Cox regression. Gene ontology (GO) and Kyoto Gene and Genomic Encyclopedia (KEGG) pathway enrichment analysis were performed using single-sample Gene set enrichment analysis (ssGSEA). Finally, analyzed to a correlation of deleted in DMBT1 expression with overall immune status, tumor purity and the expression profiles of the human leukocyte antigen (HLA) genes. Results: The HT was found to be significantly associated with sex, tumor foci, ETE, residual tumor, T stage. And the PTC concurrent with HT was a lower risk of recurrence versus the Non-HT groups. A total of 136 DEMs were identified between the HT group and Non-HT groups. Among them, the expression level of DMBT1 in the HT groups was statistically higher than that of the Non-HT groups. Between the high-expression DMBT1 versus low-expression demonstrated that the significant association with ETE, recurrence. And the DMBT1 were independent predictors for survival. The overall immune activity of high-expression of DMBT1 was higher than that of the low-expression group. Conclusions: The PTC patients with HT had better behavior features and prognosis than did those with simple PTC. The DMBT1 in PTC-HT patients were the potential possibly factors inhibit tumors. High-expression of DMBT1 may improve PTC prognosis by the immune-related pathways.